Strategi Pemasaran UMKM Kelurahan Anggut Atas dalam Menghadapi Pasar di Era Pandemi Covid-19 - Rossa Ayuni; Asmaul Husna (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to determine the Marketing Strategy of MSMEs in Anggut Atas Village in facing the market in the Covid-19 Pandemic Era. This research is oriented towards souvenir shops typical of Bengkulu located in Anggut Atas Village, Ratu Samban District, Bengkulu City, namely Ratu Samban and Akilah 2R Shops. This research uses descriptive. Sources of data in this study the author uses 2 sources, namely Primary Data and Secondary Data. The data collection technique of this research used observation, interviews, and documentation. There are 3 data analysis techniques, namely Data Reduction, Data Display, and Conclusion Drawing/Verification. The results of this study are the MSME Strategy of Ratu Samban and Akilah 2R Stores using 5 indicators, namely Product, Price, Packaging, Promotions, People. Product Strategy Ratu Samban Store maintains Product Quality and Akilah 2R Store makes product innovations. Price Strategy Ratu Samban Store has decreased its price while Akilah 2R Store has remained stable. Packaging Strategy Ratu Samban Store and Akilah 2R Store both have 2 variations of packaging. Promotion Strategy (Promotions) Ratu Samban Store markets products directly, while Akilah 2R Store uses social media & E-Commerce. The People Strategy, for the number of employees at the Ratu Samban Store and Akilah 2R Store, there was a reduction in employees and for the difference in visitors before and after the pandemic, the Ratu Samban Store and Akilah 2R Store were empty of visitors.